Protection of Consumers with Disabilities in The Public Services Sector (Legal Comparative with Australia) - Anggraini, Anna Maria Tri; Notoprayitno, Maya Indrasti (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The existence of a consumer protection law and the ratification of the CRPD by the Indonesian government is expected to guarantee the safety and comfort of consumers, including persons with disabilities. Therefore, the problem of comparative regulation and institutional, as well as the supervision of the implementation of public services for persons with disabilities, is raised in Indonesia and Australia. Australia was chosen as a comparison because this country already has a comprehensive protection system for persons with disabilities and is fully committed to providing public service facilities. This research is a prescriptive normative research using secondary data consisting of primary legal materials and secondary legal materials. This study concludes that similar to Indonesia, the formation of regulations and policies in Australia in the public service sector for persons with disabilities has reached a technical level and is carried out in a coordinated manner between the center and the regions. The basic difference is that the institutional system that handles the planning, implementation, and supervision of public services for persons with disabilities in Indonesia is separated into various ministries and/or agencies so that it requires strengthening synergies at the central and regional levels so that the implementation of public services is guaranteed optimally.